2021
DOI: 10.21203/rs.3.rs-270331/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Free-living Turning Rather Than Gait Differentiates People with Chronic Mild Traumatic Brain Injury from Controls

Abstract: Background: Physical function remains a crucial component of mild traumatic brain injury (mTBI) assessment and recovery. Traditional approaches to assess mTBI lack sensitivity to subtle deficits post-injury, which can impact quality of life, daily function and can lead to chronic issues. Inertial measurement units (IMU) provide an objective alternative for measuring physical function of gait and turning and can be used in any environment. Our recent work has found that turning quality is more sensitive than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The potential for wearable sensors to be adapted for use in a variety of populations and settings has previously been explored [ 17 ]. Numerous studies have indicated that wearable devices can be utilized to highlight gait characteristics that distinguish clinical populations such as mTBI [ 38 ] and PD [ 39 ] from control subjects, as well as assess fall risk [ 22 , 40 , 41 ]. Following further validation in clinical populations as well as in free-living environments, the AX6 may provide a cost-friendly, objective method of gait analysis in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for wearable sensors to be adapted for use in a variety of populations and settings has previously been explored [ 17 ]. Numerous studies have indicated that wearable devices can be utilized to highlight gait characteristics that distinguish clinical populations such as mTBI [ 38 ] and PD [ 39 ] from control subjects, as well as assess fall risk [ 22 , 40 , 41 ]. Following further validation in clinical populations as well as in free-living environments, the AX6 may provide a cost-friendly, objective method of gait analysis in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%